ACE2 Gene Polymorphism And Its Clinical Correlation With Biochemical Imbalance - Sukhija, Garima; Sidhu, H.K; Sharma, Narotam; Sharma, Piyusha (Journal of Neonatal Surgery, 2025)
Angiotensin converting enzyme 2 (ACE2) plays a pivotal role in the renin–angiotensin system, with emerging evidence linking its genetic variants to metabolic and hepatic homeostasis. This cross sectional study assessed the association between a common ACE2 single nucleotide polymorphism and key biochemical markers in 200 adult patients undergoing routine health evaluations. Genotyping was performed by PCR RFLP, and fasting blood samples were analysed for glycosylated hemoglobin (HbA1c), liver transaminases (SGOT/AST and SGPT/ALT), a full lipid panel (total cholesterol, HDL, LDL, triglycerides), and serum 25 hydroxyvitamin D₃. Statistical comparisons between ACE2 positive (n = 155) and ACE2 negative (n = 45) groups employed Student’s t tests, Mann–Whitney U tests, and chi square analyses as appropriate, with significance defined as p < 0.05. Carriers of the ACE2 polymorphism demonstrated a modest but statistically significant elevation in mean HbA1c (4.56 ± 1.88 % vs. 3.83 ± 1.73 %; p = 0.017), indicating a shift toward subclinical glucose dysregulation despite low prevalence of overt diabetes. SGOT levels were significantly higher among carriers (55.7 ± 21.0 IU/L vs. 46.7 ± 15.9 IU/L; p = 0.0027), while SGPT exhibited a non significant upward trend. No differences were observed in total cholesterol, HDL, LDL, or triglyceride concentrations between genotypic groups (all p > 0.05). Serum vitamin D₃ deficiency (< 20 ng/mL) was ubiquitous (≈48 % of participants) and did not differ by ACE2 status (p = 0.42). These findings suggest that ACE2 genetic variation contributes to subtle impairments in glucose handling and low grade hepatic stress, without appreciable effects on lipid metabolism or vitamin D status. Incorporation of ACE2 genotyping into risk stratification protocols could enable early identification of individuals at risk for metabolic derangements, guiding tailored lifestyle or pharmacologic interventions. Future longitudinal and mechanistic studies are warranted to determine whether ACE2 driven metabolic shifts translate into increased incidence of type 2 diabetes or hepatic pathology, and to explore the therapeutic potential of targeting the ACE2/angiotensin (1–7) axis.